2019
DOI: 10.1128/aac.01084-19
|View full text |Cite
|
Sign up to set email alerts
|

Griffithsin Retains Anti-HIV-1 Potency with Changes in gp120 Glycosylation and Complements Broadly Neutralizing Antibodies PGT121 and PGT126

Abstract: Griffithsin (Grft) is an antiviral lectin that has been shown to potently inhibit HIV-1 by binding high-mannose N-linked glycosylation sites on HIV-1 gp120. A key factor for Grft potency is glycosylation at N295 of gp120, which is directly adjacent to N332, a target glycan for an entire class of broadly neutralizing antibodies (bNAbs). Here, we unify previous work on the importance of other glycans to Grft potency against HIV-1 and Grft’s role in mediating the conformational change of gp120 by mutating nearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…In both in vitro and in vivo studies, it has been demonstrated that griffithsin’s identical carbohydrate domains can bind to the specific oligosaccharides on the envelope of viral glycoproteins [ 21 ]. The efficacy of this compound is through attachment to the various viral surface glycoproteins, such as HIV glycoprotein 120 and SARS-CoV spike glycoprotein, has been shown in previous studies [ 22 , 23 ]. In several previous studies, griffithsin also demonstrated an in vitro activity against SARS-CoV and MERS-CoV [ 24–26 ].…”
Section: Sars-cov-2 Cell Entry As Promising Targetmentioning
confidence: 90%
“…In both in vitro and in vivo studies, it has been demonstrated that griffithsin’s identical carbohydrate domains can bind to the specific oligosaccharides on the envelope of viral glycoproteins [ 21 ]. The efficacy of this compound is through attachment to the various viral surface glycoproteins, such as HIV glycoprotein 120 and SARS-CoV spike glycoprotein, has been shown in previous studies [ 22 , 23 ]. In several previous studies, griffithsin also demonstrated an in vitro activity against SARS-CoV and MERS-CoV [ 24–26 ].…”
Section: Sars-cov-2 Cell Entry As Promising Targetmentioning
confidence: 90%
“…Griffithsin, a broad‐spectrum antiviral drug, could bind to various glycoproteins on the viral surface, such as the glycoprotein 120 of HIV and the spike glycoprotein of SARS‐CoV. 72 , 73 , 74 Due to the high similarity across the spike protein of SARS‐CoV and SARS‐CoV‐2, 75 griffithsin constitutes a potential treatment choice for COVID‐19 infections. Nafamostat has also shown an antiviral activity through targeting the host protease TMPRSS2 and inhibiting the virus−host cell membrane fusion.…”
Section: Treatment Of Covid‐19mentioning
confidence: 99%
“…Griffithsin and nafamostat could block the replication of SARS‐CoV‐2 through inhibiting the virus attachment and cell entry. Griffithsin, a broad‐spectrum antiviral drug, could bind to various glycoproteins on the viral surface, such as the glycoprotein 120 of HIV and the spike glycoprotein of SARS‐CoV 72–74 . Due to the high similarity across the spike protein of SARS‐CoV and SARS‐CoV‐2, 75 griffithsin constitutes a potential treatment choice for COVID‐19 infections.…”
Section: Treatment Of Covid‐19mentioning
confidence: 99%
“…We tested three positions in the high-mannose patch, namely positions 289, 332, and 339. These positions form part of the target sites for multiple agents that inhibit HIV-1, including antibodies 2G12, 10-1074, PGT135, PGT128, and DH270.5 [54][55][56][57][58], and the lectin microbicide griffithsin [59]. Data are composed of 1,960 amino acid sequences from 109 patients infected by HIV-1 subtype C, which is the most prevalent HIV-1 clade worldwide [60].…”
Section: Prediction Of Variance Patterns In Hiv-1 Envmentioning
confidence: 99%